Fertility induction associated with improved peripheral reproductive parameters in male Prop1df/dfmice subjected to GH and levothyroxine replacement - Bruna Viscardi Azevedo; Juliana Moreira Marques; Nicholas Trigueiro; Victor Yuji Yariwake; Mariana Matera Veras; Leticia Kaory Tamashiro; Robison Cruz; Luciani R. Silveira de Carvalho (Archives of Endocrinology and Metabolism)
ABSTRACT Objective: The aim of this study was to characterize the parameters of reproductive anatomy and pituitary hormone expression levels in ames dwarf mice (Prop1df/df). Materials and methods: Male Prop1df/df mice aged 30 days received daily intraperitoneal injections of recombinant human GH and levothyroxine three times weekly for 60 days. The sexual maturation of these animals was compared with that of their wild-type (Prop+/+) and untreated (Prop1df/df) siblings. Results: The Prop1df/df treated group developed sexual maturation 2 weeks later than the Prop+/+ group and presented an increase in testicular weight, complete spermatogenesis, and enhanced LH and FSH expression. The Prop1df/df untreated group had low FSH expression and no offspring; most animals in this group did not develop sexual maturation during the study period. Conclusion: Replacement with GH and levothyroxine appeared to play a crucial role in restoring peripheral reproductive parameters and increasing pituitary hormone expression in Prop1df/df mice.